Дослідження та розробка аналітичних методів crm системи магазину побутової техніки - Нестеров, С. О. (ХНУРЕ, 2023)
This paper describes a list of methods and algorithms to research in order to develop the CRM system of the household appliances store. The list includes such methods as data clustering methods, content-based filtering, collaborative filtering, and association rules for pattern detection.